2014
DOI: 10.14693/jdi.v21i2.224
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status and Treatment Needs of Visual Impairment in Phitsanuloke, Thailand

Abstract: There is little information on the oral health status of visual impairment in Thailand. Objective: To investigate the oral health status and dental treatment needs of visual impaired Thai. Method: The subjects were 146 visual impairment (70 males and 76 females, mean age 48.8 ± 5.9), who live in Phitsanuloke, Thailand. Information on self-perceived oral health problems, oral function and oral health behavior was obtained via questionnaires. Oral examinations investigated the Decay Missing Filling Teeth (DMFT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Penelitian tersebut dilakukan di Thailand pada 146 orang tunanetra yang terdiri dari 70 orang laki-laki dan 76 orang perempuan. Berdasarkan penelitian tersebut diketahui 35% membutuhkan tambalan gigi, 12,3% membutuhkan pencabutan gigi, 34,8% memiliki penyakit periodontal dan 38% membutuhkan gigi tiruan sebagian atas dan bawah 4 .…”
Section: Pendahuluanunclassified
“…Penelitian tersebut dilakukan di Thailand pada 146 orang tunanetra yang terdiri dari 70 orang laki-laki dan 76 orang perempuan. Berdasarkan penelitian tersebut diketahui 35% membutuhkan tambalan gigi, 12,3% membutuhkan pencabutan gigi, 34,8% memiliki penyakit periodontal dan 38% membutuhkan gigi tiruan sebagian atas dan bawah 4 .…”
Section: Pendahuluanunclassified
“…A study conducted by Samnieng et al. found that visually impaired Thais have a high caries experience, periodontal disease, and poor oral hygiene 3 . The main factors for oral diseases in visually impaired individuals were plaque accumulation, lack of developing self‐help skills, inability to detect early symptoms of tooth decay, and gingival inflammation 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Establishing knowledge and good oral routines early in life are essential, particularly in visually impaired individuals 3–7 . Currently, oral hygiene instruction for the visually impaired is conducted and reinforced by dentists or dental teams using the same media as for normal‐sighted people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Visually impaired patients are unable to visualize the plaque on tooth surfaces resulting in inadequate plaque removal, progression of dental caries and inflammatory disease of the periodontium. 3 as gold standard mouthwash but it has shown several side effects like staining and taste alteration, which limit its long term use. 4 Therefore, different herbs are being widely explored to discover alternatives to synthetic antibacterial agents.…”
mentioning
confidence: 99%